2020
DOI: 10.1021/acscatal.9b05068
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Direct Enzymatic Dehydration of d-Glycerate to Pyruvate as the Key Step in Synthetic Enzyme Cascades Used in the Cell-Free Production of Fine Chemicals

Abstract: A high degree of dependence on fossil fuels is one of the major problems faced by modern societies. D-Glucose and glycerol have emerged in recent years as prospective replacements for fossil fuels used in the production of high-value chemicals, and cell-free bioproduction routes are expected to play a crucial role in such processes. Recently, several synthetic cascades used for the cell-free biotransformations of D-glucose and glycerol to pyruvate and beyond have been described. However, these were limited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…[8] However, while CcXylDHT and RlArDHT are reactive toward long sugar acid substrates (e. g. D-gluconate) we recently showed that they are practically inactive toward D-glycerate. [9] In that study, several novel dehydratases (DHADs and DHTs) with Both showed up to 50-fold higher activity toward D-glycerate when compared to SsDHAD. Further substrate profiling demonstrated however that FtDHAD, in contrast to CcXylDHT and RlArDHT, is significantly less active toward longer sugar acids (such as D-gluconate), while PuDHT is not active on branchedchain substrates such as DHIV, in contrast to SsDHAD (Table 1).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…[8] However, while CcXylDHT and RlArDHT are reactive toward long sugar acid substrates (e. g. D-gluconate) we recently showed that they are practically inactive toward D-glycerate. [9] In that study, several novel dehydratases (DHADs and DHTs) with Both showed up to 50-fold higher activity toward D-glycerate when compared to SsDHAD. Further substrate profiling demonstrated however that FtDHAD, in contrast to CcXylDHT and RlArDHT, is significantly less active toward longer sugar acids (such as D-gluconate), while PuDHT is not active on branchedchain substrates such as DHIV, in contrast to SsDHAD (Table 1).…”
Section: Introductionmentioning
confidence: 84%
“…Further substrate profiling demonstrated however that FtDHAD, in contrast to CcXylDHT and RlArDHT, is significantly less active toward longer sugar acids (such as D-gluconate), while PuDHT is not active on branchedchain substrates such as DHIV, in contrast to SsDHAD (Table 1). [9] DHTs and DHADs belong to the ilvD/EDD (isoleucine, leucine, valine Dehydratase/Entner-Doudoroff Dehydratase) superfamily of enzymes. [4,8,10] To date, there is no consistent naming system for enzymes from this superfamily, which complicates their comparative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[80] A broad substrate scope has been demonstrated for the dehydratase from Paralcaligenes ureilyticus, which is not only highly active in catalyzing the hydration of d-gluconate, d-xylonate, and l-arabinonate, [81] but is also useful for the efficient conversion of d-glyceric acid to pyruvate. [82] Dihydroxyacids such as d-glyceric acid, 2,3-dihydroxyisovaleric acid, and d-gluconic acid are also substrates of a dihydroxyacid dehydratase from Sulfolobus solfataricus. [74] Scheme 3.…”
Section: Biocatalytic Water Elimination (Dehydration)mentioning
confidence: 99%
“…The replacement of fossil fuels in the production of high value chemicals was examined by Sutiono et al (2020) with reference to cell-free bio-transformations of D-glucose and glycerol to pyruvate as a precursor for alcohols, amino acids and other building blocks. They concentrated on the slow dehydration step of D-glycerate to pyruvate catalyzed by Sulfolobus solfataricus previously incorporated into enzyme cascades and searched for alternative enzymes with higher activities, finding two distinct enzymes with greater activity and higher turnover numbers than the enzyme from S. solfataricus.…”
Section: Cell-free Enzyme Pathwaysmentioning
confidence: 99%